IMPLEMENTASI KEBIJAKAN JABATAN FUNGSIONAL PENGAWAS URUSAN PEMERINTAH DAERAH (PPUPD) - Baharuddin Thahir (Jurnal Ilmiah Wahana Bhakti Praja, 2024)
ABSTRACT. There are institutional, authority and human resources (HR) problems for government supervisors. HR concerns the individual capacity and independence of a government supervisor. Grindle theory in Ardiansyah, Aksanul Khalis, Ubaidullah. (2020, hlm. 13) indicators that the implementation of a policy is running optimally are determined by the substance of the policy and the environment in which the policy is implemented. The research uses descriptive qualitative and qualitative verification analysis strategy models. This research uses a qualitative descriptive method with an inductive approach. This method is used because it examines the consistency between policies and the implementation of PPUPD Functional Positions. This consistency pays attention to the content and environment which also colors the policy. Consistency refers to dynamic conditions, adaptation to phenomena and realities of regional government in Indonesia. data analysis with two analysis models, namely the qualitative verification analysis strategy model and the qualitative descriptive strategy model. Data analysis techniques include: Content Analysis Techniques, Selected Observation, Focused Observation, Interactive Analysis, Theme Analysis, and Critical Discourse Analysis Techniques. Based on this focus, it is known that there is a functional government supervisory position (PPUPD) in institutional aspects which is attached to regional inspectorates (provincial and district/city). The thing that makes supervision relatively difficult is because the objects being monitored/examined are regional heads or officials who administratively and in terms of personnel are the superiors of PPUPD officials. In terms of authority, it experiences limitations because it only supervises aspects of implementing government affairs but does not touch on financial and asset aspects. and in the aspect of human resources, there are limitations both in terms of quantity and quality Key Words: Policy, Functional Position, Supervision, Regional Government